Taxonomic notes on West Palaearctic species of Lauxania Latreille, Sapromyza Fallén, Calliopum Strand and Minettia Robineau-Desvoidy, with a description of a new species of Minettia (Diptera, Acalyptrata: Lauxaniidae) from Morocco - Ebejer, Martin J. (Zootaxa, 2019)
Taxonomic characters separating the genera Lauxania, Calliopum and Sapromyza are discussed. The taxonomy of Sapromyza sordida, S. halidayi and S. tuberculosa is revised. Sapromyza sordida and S. halidayi are proposed junior synonyms of S. tuberculosa, which is transferred to Calliopum, comb. nov. The Minettia punctiventris group of species is characterized and the following taxonomic changes are proposed: Minettia suillorum (Robineau-Desvoidy, 1830), = Sapromyza tinctiventris Rondani, 1868—syn. nov.; = Sapromyza muricata Becker, 1895—syn. nov.; = Sapromyza subtinctiventris Papp, 1981—syn. nov. Minettia aenigmatica sp. n. is described within this group.